2022
DOI: 10.1101/2022.01.19.22269391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and its clinical severity are associated with alterations of plasma sphingolipids and enzyme activities of sphingomyelinase and ceramidase

Abstract: In the current pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; COVID-19), a better understanding of the underlying mechanisms is essential to reduce morbidity and mortality and treat post-COVID-19 disease. Here, we analyzed alterations of sphingolipids and their metabolizing enzymes in 125 men and 74 women tested positive for SARS-CoV-2 and hospitalized with mild, moderate or severe symptoms or after convalescence. The activities of acid and neutral sphingomyelinases (ASM, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
3
3
0
Order By: Relevance
“…We found that the use of antidepressants with high FIASMA activity, comprising specific SSRI and non-SSRI molecules, was significantly less prevalent in adult inpatients who tested positive versus negative for the SARS-CoV-2 in a matched analytic sample, and significantly associated with reduced mortality. These findings are in line with prior preclinical [ 45 ] and observational [ 28 , 29 ] study results, suggesting the utility of medications with FIASMA activity against COVID-19 disease progression, as well as studies showing that plasma levels of ceramides and enzyme activities of sphingomyelinase and ceramidase strongly correlate with disease clinical severity and inflammation markers in patients with COVID-19 [ 60 , 61 , 62 , 63 , 64 ]. Inhibition of the ASM catalyzing the formation of ceramides [ 50 , 65 ] by FIASMA antidepressants may result in two effects: antiviral—through the reduced formation of ceramide-enriched membrane domains that facilitate SARS-CoV-2 entry in cells, and anti-inflammatory—through the inhibition of ASM in endothelial cells and the immune system [ 7 , 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…We found that the use of antidepressants with high FIASMA activity, comprising specific SSRI and non-SSRI molecules, was significantly less prevalent in adult inpatients who tested positive versus negative for the SARS-CoV-2 in a matched analytic sample, and significantly associated with reduced mortality. These findings are in line with prior preclinical [ 45 ] and observational [ 28 , 29 ] study results, suggesting the utility of medications with FIASMA activity against COVID-19 disease progression, as well as studies showing that plasma levels of ceramides and enzyme activities of sphingomyelinase and ceramidase strongly correlate with disease clinical severity and inflammation markers in patients with COVID-19 [ 60 , 61 , 62 , 63 , 64 ]. Inhibition of the ASM catalyzing the formation of ceramides [ 50 , 65 ] by FIASMA antidepressants may result in two effects: antiviral—through the reduced formation of ceramide-enriched membrane domains that facilitate SARS-CoV-2 entry in cells, and anti-inflammatory—through the inhibition of ASM in endothelial cells and the immune system [ 7 , 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…b Models were adjusted for sex, age, race and ethnicity, obesity, number of diagnoses, history of mood or anxiety disorder, history of other psychiatric disorders, number of home medications, concurrent exposure to benzodiazepine or Z drug, concurrent exposure to antipsychotic drugs, and concurrent exposure to non-antidepressant drugs with FIASMA or S1R activity (listed in Table S1). markers [42][43][44][45], lending further support for FIASMA as an explanatory mechanism behind the associations reported in observational studies.…”
Section: Discussionsupporting
confidence: 56%
“…The COVID-19 pandemic is still regarded as a leading concern due to its deleterious effects on public health, healthcare infrastructure, and the economy [1][2][3][4][5][6]. There remains an unmet need for effective outpatient treatments for Coronavirus Disease 2019 (COVID- 19), particularly for low-and middle-income countries, especially treatments that can be taken orally, have few medical contraindications [7,8], and are well-tolerated, affordable and readily available [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%